Effect of seedling size on post-planting growth and survival of five Mexican Pinus species and their hybrids - Ponce-Figueroa, José Alberto; Antúnez, Pablo; Hernández-Díaz, José Ciro; Prieto-Ruíz, José Ángel; Carrillo-Parra, Artemio; López-Serrano, Pablito Marcelo; Wehenkel, Christian (PeerJ, 2024)
Background Seedling growth and survival depend on seedling quality. However, there is no experimental evidence showing that the seedling dimensions of the abundant, economically important and widely distributed tree species Pinus arizonica, P. durangensis, P. engelmannii, P. leiophylla, and P. teocote and their hybrids effectively improve survival and growth in reforestations and plantations in Mexico. Therefore, the aim was to evaluate the influence of initial morphological parameters of 2,007 nursery seedlings of these species and their hybrids on their growth and survival 44 months after planting in the Sierra Madre Occidental, Mexico. Methods Spearman’s coefficient (rs) and the unbiased conditional pseudo coefficient of determination (R2c) between each specific predictor and each response variable and their 95% confidence interval (CI95%) were determined using Random Forest, generalized linear model, and bootstrapping. By bootstrapping, the potential environmental heterogeneity inside the trial fields and its impact on the results were also quantified. Results Among the studied species and their hybrids moderate correlations were observed between the nursery seedling dimensions and the plant dimensions 44 months after planting. However, only weak significant correlations were found between survival rate (SR) and height (H) (rs = 0.10) and between SR and robustness index (HRCD) both before planting (rs = 0.06). Also, weak significant R2c values of the seedlings RCD, H and HRCD were detected with respect to the corresponding RCD, H and SR 44 months after planting, respectively. Furthermore, the predictor variable “seed provenance” (with 23 provenances) significantly explained the variation in the post-planting RCD, H and SR of the seedlings, with R2c values ranging from 0.10 to 0.15. The low width of the CI95% shows that the environmental conditions in the trial fields were quite homogeneous. Discussion The results also show that the inclusion of “confounding” variables in the statistical analysis of the study was crucial. Important factors to explain this low association could be the strong damage observed caused by pocket gopher, the typically low winter-spring precipitation in both field trials and adaptation factors. The study findings provide preliminary insights and information aimed at helping to design more appropriate standards for nurseries.
Keywords: Seedling quality; Seed provenance; Random Forest; Unbiased conditional coefficient of determination; Seedling dimension; Microhabitat; Environmental heterogeneity; Trial field